Use of STAX data in global-scale simulation of 133Xe atmospheric background. (October 2022) - Generoso, Sylvia; Achim, Pascal; Morin, Mireille; Gross, Philippe; Douysset, Guilhem
Abstract: A global-scale simulation of the 133 Xe atmospheric background is automated at the French National Data Center (NDC) for the purpose of categorizing the radionuclide measurements of the Comprehensive Nuclear-Test-Ban Treaty (CTBT) International Monitoring System (IMS). These simulations take into account 133 Xe releases from all known major industrial emitters in the world, compiled from the literature and described as constant values. Emission data measured directly at the stack of the Institute for Radio Elements (IRE), a medical isotope production facility located in Fleurus (Belgium), were implemented in the simulations with a time resolution of 15 minutes. This work discusses the contribution of real (measured) emissions to the prediction of the 133 Xe atmospheric background at IMS noble gas stations and at a location near Paris, for which IMS-like 133 Xe measurements were available. For the purpose of this study, simulations initiated with the IRE measured emissions were run in parallel to those with the a priori emissions used to date. The benefits of including actual emissions in the simulations were found as a function of the distance between the station and the source of the release. At the closest stations, i.e., near Paris (France) and at Schauinsland, Freiburg (Germany), respectively 250 and 400 km from Fleurus, the simulated activity concentrations differed by a factor greater than 2 more than one third of the time, and by a factor of more than 5 about 10% of the time. No significant or detectable differences were found beyond 1500–2000 km. Furthermore, at the Paris station, the timing of the measured peaks was better reproduced with the actual emission data. However, not all peak amplitudes were correctly reproduced even though the real emissions were used, highlighting the remaining uncertainties, primarily in the meteorological data and transport modeling. Highlights: Radioxenon emissions measured at IRE by the STAX system were included in automated atmospheric transport simulations. Simulated and measured 133 Xe activity concentrations at monitoring stations during nearly one year were analyzed. STAX emissions influenced simulation results below 1500-2000 km from the source, notably improving peak timings. Amplitudes were not all reproduced with the use of real emissions, pointing to other sources of uncertainty to address.